Correlation between Clinical Symptoms of Various Colorectal Diseases and Colonoscopic Findings - Kidwai, Roman; Sharma, Anup (Journal of Nepalgunj Medical College, 2019)
Background: About 30% of patients presenting to surgical outpatient department has lower gastrointestinal (LGI) symptoms. Colonoscopy is a low risk and at the same time investigation of choice in these patients which allows visualization of the entire colon and the terminal portion of ileum. This study was done to find out the diagnostic accuracy of colonoscopy in relation to the clinical symptoms of the disease. Methods: This was a prospective, hospital based study from February 2014 to March 2019 carried out at Nepalgunj Medical College and Teaching Hospital. The colonoscopy diagnosis was compared with the clinical symptoms and further confirmed with histological examination. Results: 341 patients underwent colonoscopy. There were 234 (68.62%) males and 107 (31.37%) females with the male to female ratio of 2.18: 1. The age ranged from 16 to 81 with the mean age of 59.63±10.37. The most common presenting symptom was per rectal bleeding (40.34%) the after were alteration in bowel habit (17.30%), constipation (12.90%), hematochezia (11.43%). The least common indication for colonoscopy was unexplained anemia. Haemorrhoids were the most common findings consisting 32.55%. In 19.94% it was normal. Majority had various inflammatory conditions, among them 10.85% had proctocolitis, 2.34% were suspected to have ulcerative colitis. There were 17(4.98%) patients with colonic and 13(3.18%)with rectal carcinoma. 10.55% had colorectal polyps. Out of 111 patients suspected to have hemorrhoids clinically 102 had same findings on colonoscopy. Similarly 34 patients presenting with chronic diarrhea with bleeding and 59 with alteration in bowel habit where inflammatory conditions were suspected had similar findings on colonoscopy in 29 and 34 patients respectively. Similarly the suspicion of malignancy on clinical basis was also correlated on colonoscopy. The inflammatory conditions diagnosed on colonoscopy were confirmed in 85.04 % by histology. Similarly malignancy and the presence of polyps diagnosed on colonoscopy were confirmed by histology in 97.05% and in 97.22% cases respectively. Conclusion: Colonoscopy is a safe and effective investigation to diagnose various colorectal conditions. There was a correlation between the clinical symptoms and the colonoscopicdiagnosis especially in conditions like inflammatory and neoplastic colorectal diseases. When combined with histology the diagnostic accuracy can be near 100% in conditions like inflammatory and benign or malignant diseases.